Teachers’ Learning Profiles in Learning Programming: The Big Picture! - Saqr, Mohammed; Tuominen, Ville; Valtonen, Teemu; Sointu, Erkko; Väisänen, Sanna; Hirsto, Laura (Frontiers in Education, 2022)
Currently there is a need for studying learning strategies within MOOCs focused on staff professional development, especially the context of teachers’ in-service training is and unstudied area. This study response to this need to understand how in-service teachers approach and regulate their learning during a professional Massive Open Online Course. In particular, it examines the strategies used by the in-service teacher when they have to study programming, how to teach programing. The study implemented a combination of unsupervised clustering and process mining in a large course (n=27,538 of which 8,547 completed). The results, in-service teachers’ learning strategies, shows similar trends compared to previous studies conducted within MOOCs, indicating that teachers would not appear different from the other groups of students based on their learning strategies. Rather, they are a heterogeneous group when they approach and regulate their learning. Three subgroups (efficient (N=3596, 42.1%), clickers (n=1785, 20.9%), and moderates (N=3166, 37%)) were found with different strategies. The efficient students finished the course in a short time, spent more time on each lesson, and moved forward between lessons. The clickers took longer to complete the course, repeated the lessons several times, and moved backwards to revise the lessons repeatedly. As such, our findings indicate a significant fraction within teachers’ poorly regulate their learning, providing important aspects that need to be considered as part of teachers training.